Combating security breaches and criminal activity in the digital sphere - Geetha, S. 1979-; Phamila, Asnath Victy 1978- (Advances in digital crime, forensics, and cyber terrorism (ADCFCT) book series, 2016)
"This book is a pivotal reference source for the latest scholarly research on current trends in cyber forensic investigations, focusing on advanced techniques for protecting information security and preventing potential exploitation for online users"-Provided by publisher